FDZ data description: Real-estate data for Germany campus files (RWI-GEO-RED Panel and RWI-GEO-RED Cross v5) - Advertisements on the internet platform ImmobilienScout24 for teaching purposes - Sandra Schaffner; Patrick Thiel (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
The FDZ Ruhr provides two campus files on real estate advertisements in Germany: the Panel Campus File (RWI-GEO-RED Panel) and a Cross-Sectional Campus File (RWI-GEO-RED Cross-Section). The datasets are extractions of the Scientific Use Files of RWI-GEO-RED. The Panel File covers the 15 largest cities in Germany over the whole time period, whereas the Cross-Section File covers all of Germany within one year (2023). The RWI-GEO-RED data are based on information from the internet platform ImmobilienScout24 and cover residential advertisements only. The campus files include apartments for sale and for rent and houses for sale. The data are available for lectures, tutorials, seminar thesis, bachelor and master thesis and scientific research. The provided dataset covers detailed regional information and a rich set of housing characteristics. Both datasets are samples drawn and not comprehensive databases like the Scientific Use File. The already implemented data cleaning eases the data work for students. This data report gives a brief overview of the data as well as its limitations and specifics. The data report is addressed to (potential) users of the data as support for their data preparation. This data report is an updated version of previous reports and refers to the Campus Files v5, which covers data until 2023. – – Das FDZ Ruhr stellt zwei Campus-Dateien zu Immobilienanzeigen in Deutschland zur Verfügung: Das Panel Campus File (RWI-GEO-RED Panel) und ein Cross-Sectional Campus File (RWI-GEO-RED Cross). Die Datensätze sind Auszüge aus den Scientific Use Files von RWI-GEO-RED. Das Panel File umfasst die 15 größten Städte in Deutschland über den gesamten Zeitraum, während das Cross-Section File ganz Deutschland innerhalb eines Jahres (2023) abdeckt. Die Daten von RWI-GEO-RED beruhen auf Informationen der Internetplattform ImmobilienScout24 und umfassen ausschließlich Wohnungsanzeigen. Die Campus-Dateien enthalten Wohnungen zum Kauf und zur Miete sowie Häuser zum Verkauf. Die Daten stehen für Vorlesungen, Tutorien, Seminar-, Bachelor- und Masterarbeiten sowie für die wissenschaftliche Forschung zur Verfügung. Der bereitgestellte Datensatz umfasst detaillierte regionale Informationen und eine Vielzahl von Wohnungsmerkmalen. Bei beiden Datensätzen handelt es sich um eine Stichprobe und nicht um eine umfassende Datenbasis wie beim Scientific Use File. Die bereits implementierte Datenbereinigung erleichtert den Studierenden die Arbeit mit den Daten. Die vorliegende Datenbeschreibung gibt einen kurzen Überblick über die Daten sowie über ihre Grenzen und Besonderheiten. Die Datenbeschreibung richtet sich an (potentielle) Nutzende der Daten als Unterstützung für deren Datenaufbereitung. Die Datenbeschreibung bezieht sich auf die Version V5 beider Datensätze.
Keywords: 330